Description of the attitudes of female students toward human papillomavirus (HPV) vaccination - Nadya Juliaty Kacaribu; Chreisye K. F. Mandagi; Afnal Asrifuddin (JOURNAL OF Mental Health Concerns, 2026)
Background: Cervical cancer is a significant global health problem, with most cases caused by infection with oncogenic types of Human Papillomavirus (HPV). In Indonesia, HPV immunization coverage remains suboptimal. Female university students, as agents of change, are expected to play an active role in prevention through their knowledge, attitudes, and practices regarding HPV immunization. Purpose: To describe the behavior of female students toward HPV immunization, including knowledge, attitudes, and practices. Method: A quantitative descriptive design with a cross-sectional approach. The population consisted of all active female students from the 2021–2025 cohorts, totaling 990 individuals. A sample of 102 respondents was determined using the Lem show formula and selected through stratified random sampling. Data were collected using an online questionnaire (Google Form) that had been tested for validity and reliability. Data analysis was conducted univariately to describe the frequency distribution of each variable. Results: The results showed that most respondents had a moderate level of knowledge (38.2%), followed by low (32.4%) and good (29.4%) levels. Attitudes toward HPV immunization were overwhelmingly positive (98.0%), with only 2.0% showing negative attitudes. However, none of the respondents (0%) had received the HPV vaccine, although the majority (77.5%) expressed willingness to be vaccinated if it were available. Conclusion: The knowledge of female students is generally moderate, and their attitudes toward HPV immunization are highly positive; however, this is not reflected in actual vaccination behavior. There is a gap between intention and practice, indicating the need for more effective interventions to improve access and promote HPV vaccination uptake. Keywords: Attitude; Cervical Cancer; Female Students; HPV; Immunization; Knowledge; Practice.